STRATEGIC POLICIES OF THE WEST LOMBOK REGIONAL GOVERNMENT IN INCREASING TOURIST INTEREST TO REVISIT THE SENGGIGI AREA AND ITS SURROUNDINGS: Kebijakan Strategis Pemerintah Daerah Lombok Barat Dalam Meningkatkan Minat Wisatawan untuk Berkunjung Kembali ke Kawasan Senggigi dan Sekitarnya - I Gusti Ngurah Octova Seventilofa (PESOLAH: Jurnal Pendidikan, Sosial dan Humaniora, 2025)
Tourism plays a crucial role in regional economic development, particularly in areas with abundant natural and cultural resources. Senggigi, an iconic tourism destination in West Lombok Regency, has experienced a significant decline in tourist visits since 2018 due to natural disasters, the COVID-19 pandemic, weak digital promotion, and competition from emerging destinations such as Mandalika. This study aims to analyze the strategic policies of the West Lombok Regional Government in revitalizing Senggigi as a leading tourism destination. The study employs a descriptive approach by analyzing literature, statistical data, and field observations. Findings indicate that the decline in tourist visits is associated with inadequate infrastructure, weak branding, and underutilized local tourism potential. Strategic recommendations include infrastructure revitalization, rebranding campaigns, community-based tourism development, diversification of tourism products, and multi-stakeholder collaboration. The planned implementation of these policies is expected to restore Senggigi as a competitive and sustainable destination in Lombok